Nurses' Numeracy and Graphical Literacy: Informing Studies of Clinical Decision Support Interfaces. Issue 2 (April 2016) - Lopez, Karen Dunn; Wilkie, Diana J.; Yao, Yingwei; Sousa, Vanessa; Febretti, Alessandro; Stifter, Janet; Johnson, Andrew; Keenan, Gail M.
Abstract : We present findings of a comparative study of numeracy and graph literacy in a representative group of 60 practicing nurses. This article focuses on a fundamental concern related to the effectiveness of numeric information displayed in various features in the electronic health record during clinical workflow. Our findings suggest the need to consider numeracy and graph literacy when presenting numerical information as well as the potential for tailoring numeric display types to an individual's cognitive strengths. Abstract : Supplemental Digital Content is Available in the Text.